National key economic area multiplier impact on Malaysian economy: An input-output analysis - Ahmad Fuad, Siti Nadiah; Puasa, Ahmad Fauzi (2011)
The ultimate aim of this research is to provide an analysis of the impact multipliers on the Malaysian economy for 12 NKEAs sectors. Economic activity is a complicated web of interdependent behavior. A change in any part of the economy leads to changes elsewhere. Consequently, estimation of the ultimate total impact of a change in NKEAs requires measurement of the changes that occur elsewhere in the economy. The technique available to obtain these measurements is called input-output (I‐O) analysis. I-O analysis is concerned with studying the interdependence of the producing and consuming units in the modern economy. Our computation of complete I‐O multipliers includes total output, income, employment, value‐added, imported commodity, domestic taxes and imported taxes multipliers for the NKEAs. Among the NKEAs sectors, the Palm Oil, Tourism, Education, Healthcare and Other sectors have great potential for further development and are expected to give high impact on the Malaysian economy. If government wishes to boost up the Malaysian economic for the growth, these are the appropriate sectors for development.